Pengembangan mata pencaharian alternatif berkelanjutan: diversifikasi produk ikan air tawar di Kampung Boha Dan Pachas Distrik Muting Kabupaten Merauke: Development of sustainable alternative livelihoods: diversification of fresh water fish products in Boha and Pachas Villages, Muting District, Merauke Regency - Yuanike Kaber; Antoni Ungirwalu; Jonni Marwa; Calvyn S. Pakidi; Bony Lantang; Sisca Elviana; Astaman Amir; La Ode A. S. Mando; Aminuddin M. Kandari (IGKOJEI: Jurnal Pengabdian Masyarakat, 2023)
ABSTRACT Merauke Regency is an Autonomous Regency located at the eastern end of Indonesia which is directly adjacent to Papua New Guinea (PNG). This region has the peculiarities of both its ecology and its people. Muting District is one of the areas in Marauke which has the potential for freshwater fish because it is located in the Bian Lake wildlife reserve. Together with partners the Peat and Mangrove Restoration Agency of the Republic of Indonesia (BRGM) as a consortium partner of the Indonesian Forest Management Community (KOMHINDO) in 2022 to obtain funding for a vocational campus which involves three universities, namely the University of Papua, Musamus University and Halu Oleo University. One of the objectives of this activity is the Teaching Factory for the development of sustainable alternative livelihoods based on fisheries and forestry resources for poverty alleviation. This activity was centred in Boha and Pachas Villages, Muting District, Merauke Regency, South Papua. The results of the Training and Productive Economic Development Program for Local Communities Based on Fisheries and Forestry Resources are in the form of fish product diversification in the form of making fish sauce, meatballs and empek-empek. The participation of the UMK groups from Pachas and Boha villages was very enthusiastic and took part in the training which is expected to be used as a source of community economic income in the future. Key words: Kedaireka; Matching fund; Merauke; UNIPA